Penerapan Algoritma XGBoost Dalam Prediksi Harga Sewa Kos Di Kota Samarinda - Amalia Rahman; Amelia Yusnita; Hanifah Ekawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The population growth and increasing economic activity in Samarinda City have led to a rising demand for temporary housing such as boarding houses. However, rental price determination is still largely based on the owner’s intuition rather than objective factors such as available facilities, room specifications, transportation accessibility, and proximity to public amenities. This study aims to develop a rental price prediction model for boarding houses using the Extreme Gradient Boosting (XGBoost) algorithm with a Knowledge Discovery in Database (KDD) approach. The research data were collected through a web scraping process from the Mamikos platform, yielding 231 initial records, which were then cleaned and filtered for outliers, resulting in 225 valid data points. Five main features derived from feature engineering were utilized in the model, namely Facility Score, Combined Specification Score, Nearest Place Score, Transportation Score, and Rental System Score. The evaluation results show that the XGBoost model achieved a Mean Absolute Error (MAE) of Rp348,822, a Root Mean Squared Error (RMSE) of Rp416,139, and a coefficient of determination (R²) of 0.612. These values indicate that the model can explain 61.2% of the variation in rental prices with reasonably good predictive performance. The feature importance analysis reveals that Facility Score and Combined Specification Score are the most influential factors affecting rental prices, while transportation and rental system factors contribute less significantly. This study is expected to serve as a reference for boarding house owners, tenants, and policymakers in determining more objective and competitive rental prices based on a data mining approach.